(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2009)
The Venezuela government within its economic and social policies establishes a profile based on the socialist principle of cooperation as a vital exchange between the development of man and society. Surge in March 2004 and Vuelvan Caras spearhead the understanding he endogenous economic development as the way citizens use their land resources potential and the collective good. That is why the aim of this study is to assess the management and productivity management Cooperatives Vuelvan Caras Aragua State, Venezuela, as a starting point for the proposed management strategies of endogenous development. The investigation is related to the evaluative, descriptive approach grounded in a design field. The study population consisted of 796 cooperatives Vuelvan Caras, funded by the Ministry of People’s Power for Communal Economy. Sample was taken as 149 cooperatives belonging to the Nuclei of Endogenous Development (NUDE), to finally work with a sub-sample of 32 cooperatives intentional active. The technique of data collection was the survey instrument and as a questionnaire. The data were analyzed by descriptive statistical tables often simple. As a result it was found that: Cooperatives with funding are not delivering productivity to the level of endogenous development required in Aragua state, since only there are fifteen NUDE. Therefore, it recommends a set of managerial strategies that contribute to the facilitation of endogenous development and management within cooperatives